TRANSLATION TECHNIQUES IN TAJ: TRAGEDI DI BALIK TANDA CINTA ABADI NOVEL - Rosita, Nur (English Department FBS UNP, 2016)
TRANSLATION TECHNIQUES IN TAJ: TRAGEDI DI BALIK TANDA CINTA ABADI NOVELTEKNIK PENERJEMAHAN DALAM NOVEL TAJ: TRAGEDI DI BALIK TANDA CINTA ABADIAbstractTranslation requires reputable competence when it is related with the translation quality: how accurate, clear, and readable the translator delivers the message. The quality of translation is closely related with the techniques used by the translator to tackle many obstacles in doing translation. Each technique used gives different impact in translation product. The translator has to choose the appropriate techniques in order to deliver the message accurately, clearly, and readable. This project was descriptive research which has been attempted to analyze the techniques used in translating historical romance novel Taj: A Story of Mughal India into Taj: Tragedi Di Balik Tanda Cinta Abadi by Maria M. Lubis. It used three variable factors of translation that were the two novels as objective factor, the translator as genetic factor, and the raters as affective factor to analyze, compare, rate, and score the translation techniques. The data chosen from the both novel were the sentence of both novel that consist of cultural specific items. From the analysis, it was found that there were 15 techniques used in translating the novel. These 15 techniques were adaptation 19.15%, pure borrowing 18.62%, established equivalent 9.57%, natural borrowing 8.51%, generalization 6.38%, Modulation 5.85%, particularization 5.85%, amplification 5.32%, transposition 2.66%, reduction 2.13%, inversion 2.13%, pure borrowing plus established equivalent 2.13%, description 1.60%, literal 1.60%, omission 1.60%, adaptation, pure borrowing, and omission 1.06%, amplification and pure borrowing 1.06%, natural and pure borrowing 1.06%, discursive creation, generalization and transposition, literal and generalization, pure borrowing and generalization, pure borrowing and transposition, generalization and omission, adaptation, pure borrowing and transposition each of them 0.53%. The result of research showed that the dominant technique used is adaptation since the cultural term of source language is appropriate to be translated as same equivalent into the target language.Key words: translation, translation techniques, historical romance novelÂ AbstrakPenerjemahan membutuhkan kemampuan yang tinggi saat dikaitkan dengan kualitas penerjemahan: seberapa akurat, jelas, dan terbaca seorang penerjemah menyampaikan pesan dari bahasa sumber kedalam bahasa target. Qualitas terjemahan erat kaitannya dengan teknik yang digunakan untuk memecahkan kesulitan-kesulitan dalam penerjemahan. Masing-masing teknik tersebut berdampak berbeda terhadap hasil terjemahan. Penerjemah harus mampu memilih teknik yang tepat agar pesan yang disampaikan akurat, jelas, dan terbaca. Penelitian deskriptif ini bertujuan untuk menganalisa teknik dalam penerjemahan novel Taj: A Story of Mughal India kedalam Taj: Tragedi Di Balik Tanda Cinta Abadi oleh Maria M. Lubis. Penelitian ini menggunakan 3 faktor variable: kedua novel sebagai objektif faktor, penerjemah sebagai genetik faktor, dan informan sebagai afektif faktor untuk menganalisa, membandingkan, mengukur, dan menilai teknik penerjemahan. Data yang diambil dari kedua novel adalah berupa kalimat yang berisi istilah budaya. Dari hasil analisa ditemukan bahwa terdapat 15 jenis teknik yang digunakan dalam menerjemahkan novel ini. Teknik penerjemahan tersebut adalah adaptation 19.15%, pure borrowing 18.62%, established equivalent 9.57%, natural borrowing 8.51%, generalization 6.38%, Modulation 5.85%, particularization 5.85%, amplification 5.32%, transposition 2.66%, reduction 2.13%, inversion 2.13%, pure borrowing plus established equivalent 2.13%, description 1.60%, literal 1.60%, omission 1.60%, adaptation, pure borrowing, and omission 1.06%, amplification and pure borrowing 1.06%, natural and pure borrowing 1.06%, discursive creation, generalization and transposition, literal and generalization, pure borrowing and generalization, pure borrowing and transposition, generalization and omission, adaptation, pure borrowing and transposition each of them 0.53%. Dapat disimpulkan bahwa teknik yang paling banyak digunakan adalah adaptation dikarenakan istilah budaya lebih tepat diterjemahkan dengan mengganti elemen budaya pada bahasa sumber dengan hal yang sama pada budaya bahasa target.Â Kata kunci: Penerjemahan, teknik penerjemahan, novel roman sejarah